2015
DOI: 10.11646/phytotaxa.203.1.9
|View full text |Cite
|
Sign up to set email alerts
|

Bellevalia koyuncui sp. nova (Asparagaceae): a new species from South Eastern Anatolia, Turkey

Abstract: Bellevalia Lapeyrouse (1808: 425) is a genus comprising about 65 species and subspecies distributed over the Mediterranean region (Bareka et al. 2008, Jafari & Maassoumi 2008, Borzatti von Loewenstern et al. 2013).       Wendelbo (1984) reported 18 taxa, seven of which endemic to the country. In further studies, Wendelbo (1985) reduced Bellevalia latifolia Feinbrun (1940: 369) to a synonym of B. olivieri (Baker 1874: 8) Wendelbo (1985: 120). Since then, three species were published by Özhatay (2000), while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 11 publications
0
10
1
1
Order By: Relevance
“…comm.). Only B chromosomes were sometimes observed in diploids such as Bellevalia saviczii Woronow, 1927 with 2n = 8 + 1B (Gettner, 2005) and Bellevalia koyuncui Karabacak & Yildirim, 2015 with 2n = 8 + 2B (Karabacak et al 2015). The occurrence of aneuploidy in a polyploid context, associated with vegetative reproduction, may indicate chromosomal changes in process providing evolutionary potential, as presumed for B-chromosomes (Johnson 2003, Weiss-Schneeweiss and Schneeweiss 2013, Bareka et al 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…comm.). Only B chromosomes were sometimes observed in diploids such as Bellevalia saviczii Woronow, 1927 with 2n = 8 + 1B (Gettner, 2005) and Bellevalia koyuncui Karabacak & Yildirim, 2015 with 2n = 8 + 2B (Karabacak et al 2015). The occurrence of aneuploidy in a polyploid context, associated with vegetative reproduction, may indicate chromosomal changes in process providing evolutionary potential, as presumed for B-chromosomes (Johnson 2003, Weiss-Schneeweiss and Schneeweiss 2013, Bareka et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Some of these new described species are diploids (2n = 2x = 8), such as Bellevalia leucantha K. Persson, 2006, Bellevalia malatyaensis Uzunhisarcikli & Duman, 2013 and Bellevalia koyuncui Karabacak & Yildirim, 2015 (Persson 2006, Uzunhisarcikli et al 2013, Karabacak et al 2015). Polyploid species such as Bellevalia pseudolongipes Karabacak & Yildirim, 2014 (Karabacak et al 2014), Bellevalia clusiana Grisebach, 1844 (Yaylaci et al 2009) and Bellevalia edirnensis N.Özhatay & Mathew, 1991 (Özhatay et al 1991b) were identified as triploid, tetraploid and hexaploid respectively.…”
Section: Introductionmentioning
confidence: 99%
“…is a genus of bulbous plants belonging to Asparagaceae, subfamily Scilloideae, tribe Hyacintheae (APG III 2009, Chase et al 2009. The genus is distributed over the Mediterranean region from Morocco and Algeria eastwards to the Caucasus and Iran (Ozhatay et al 1991, Bareka 2008, Jafari and Maassoumi 2008, Borzatti von Loewenstern et al 2013, Karabacak et al 2014, 2015 and 74 species are listed (Govaerts 1996). The largest number of species in the genus is found in the Irano-Turanian phytogeographical region (Feinbrun 1938).…”
mentioning
confidence: 99%
“…The largest number of species in the genus is found in the Irano-Turanian phytogeographical region (Feinbrun 1938). In Turkey, Bellevalia is represented by 28 taxa, 17 of which are endemic to the country (Wendelbo 1984, Davis et al 1988, Ozhatay and Kultur 2006, Ozhatay et al 2009, 2011, Guner et al 2012, Uzunhisarcıklı et al 2013, Gurdal et al 2014, Karabacak et al 2014, 2015.…”
mentioning
confidence: 99%
“…The genus is represented by 4 sections with 45 species according to Feinburn-Dothan. When distribution and endemic regions are examined, the Irano-Turanian region is observed as the main area for species distribution, while Iran and Turkey are introduced as areas where new species are to be expected (Feinburn-Dothan, 1940).The genus is represented by 6 sections (Feinbrun-Dothan, 1940;Persson and Wendelbo, 1979;Wendelbo, 1980) with approximately 70 species according to studies published around the world (Gürdal et al, 2014;Karabacak et al, 2014Karabacak et al, , 2015. The richness in the diversity of the species lies in its distinctive characteristics regarding leaf width and pubescence, raceme shape and density, pedicel length in relation to perianth length, perianth length, the tube:lobe ratio, perianth color, and anther color (Cowley et al, 1994).Within the Flora of Turkey, there are 18 species, 7 of which are endemic (Wendelbo, 1984).…”
mentioning
confidence: 99%